The effects of ractopamine-HCl (Optaflexx) on performance, carcass characteristics, and meat quality of finishing feedlot heifers - M.J. Quinn; M.L. May; James S. Drouillard; Christopher D. Reinhardt; Brandon E. Depenbusch (Kansas Agricultural Experiment Station Research Reports, 2007)
Beta-adrenergic agonists are commonly used in livestock production to accelerate growth by enhancing lean tissue gain. These compounds repartition nutrients away from fat deposition and toward protein accretion. Generally, increased growth is associated with ractopamine feeding, which improves feed conversion and increases body weight gain. However, little data exists on the effects of ractopamine-HCl on live performance or carcass characteristics of beef heifers. Data released from Elanco Animal Health indicate that differences between gender may exist in response to ractopamine, and therefore appropriate strategies for the administration of this compound must be defined for heifers independent of those for steers. The objective of this study was to determine the effects of Optaflexx, when fed for different dosages over different durations, on finishing heifer performance.
Keywords: Cattlemen& #x27; s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Optaflexx; Heifers